PENGARUH KOMPOS BIOMASSA GULMA DAUN LEBAR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI KERITING PADA TANAH ALUVIAL - Elvidius Elvidius; Setia Budi; Dwi Zulfita (Perkebunan dan Lahan Tropika, 2022)
This research aimed to know the influence of broad leaf weeds biomassa compos and the exact dose toward the growth and the result of curly cabbage on aluvial land. This research was conducted in the farm of agriculture faculty in Tanjungpura university from 6 july 2013 until 14 august 2013. This research used field experiment method with randomized system, consists of 6 treatments and 4 tests, each test consists of 3 sample of plants. The treatments are: k0 = without give compos, k1 = give compos about 38,43 g /polybag same with 4720 kg/ha, k2 = give compos about 74,43 g /polybag same with    8720 kg/ha, k3 = give compos about 110,43 g /polybag same with 12720 kg/ha, k4 = give compos about 146,43 g /polybag same with 16720 kg/ha, k5 = give compos about 182,43 g /polybag same with 20720 kg/ha. The variable that has examined is the volume of root (cm3), amount of leaf clorofil (spad unit), wide of leaf (cm2), weight of dry plant s(g), weight of fresh plants(g), weight of leaf (sheet). The result of this research shows that the given of biomassa weeds broad leaves compos can increase the growth of mustrad greens on aluvial land. Biomassa weeds broad leaves compos is effective for the growht and result of mustrad greens on aluvial land is with dose 38,43 g/polybag.